Brain reserve in memory regions is associated with the preservation of autobiographical memories after electroconvulsive therapy - Mathiassen, André Beyer; Lundsgaard, Christoffer Cramer; Gbyl, Krzysztof; Miskowiak, Kamilla; Fagerlund, Birgitte; Larsson, Henrik B. Wiberg; Lindberg, Ulrich; Videbech, Poul (Frontiers in Psychiatry, 2025)
BackgroundElectroconvulsive therapy (ECT) may cause anterograde and autobiographical amnesia. Identifying reliable predictive biomarkers for the risk of this memory loss may assist clinicians in their decision to use this treatment. We aimed to investigate whether the baseline volume or the cortical thickness of the predetermined regions of interest (ROIs) involved in memory recall is correlated with the degree of amnesia after ECT.MethodIn this longitudinal study, we followed 19 inpatients receiving ECT for depression. Using 3-T MRI, we performed structural brain scans prior to ECT. We also assessed the autobiographical, verbal, and visual anterograde memory both before and after ECT. We conducted one-sided partial correlation analyses between the volume or the cortical thickness of the ROIs at baseline and the memory decline following ECT (ClinicalTrials.gov: NCT04160286).ResultsAs hypothesized, a larger baseline cortical thickness of the right parahippocampal gyrus (r = 0.517, p = 0.014) and the left ventrolateral prefrontal cortex (r = 0.530, p = 0.012) correlated with less ECT-related decline in autobiographical memory, respectively explaining 26.7% and 28.1% of the variance. Unexpectedly, a smaller volume of the right hippocampus also correlated with less autobiographical memory decline (r = −0.416, p = 0.048). None of the ROIs predicted anterograde memory impairment.ConclusionThese early findings suggest that a pre-ECT neural reserve in the brain regions subserving memory might act protectively against the development of autobiographical memory loss after ECT. If replicated in larger samples, our findings may have promising clinical implications as a structural MRI scan prior to ECT might contribute to determining the individual risk of autobiographical memory loss following ECT.